Identifying and Analyzing Moral Evaluation Frames in Climate Change Blog Discourse - Diakopoulos, Nicholas; Zhang, Amy; Elgesem, Dag; Salway, Andrew (Proceedings of the International AAAI Conference on Web and Social Media, 2014)
Media frames define distinctive perspectives or ways of communicating about issues and can be manifested through patterns of language use, such as preferences for various key terms and phrases. In this work we develop a novel operationalization of moral evaluation frames and study their use within a corpus of blogs discussing climate change. We compare moral evaluation frames between blogs marked as climate change skeptics and climate change acceptors. We develop a text visualization tool called Lingoscope that allows the user to observe and filter the contextual terms that convey moral framing across large volumes of text, as well as to drill down to specific examples. By focusing on climate-related topics and how they are discussed by climate change skeptics versus climate change acceptors, our approach uncovers and explores how numerous topics are framed in a different moral light in skeptical and acceptor blogs.